2022
DOI: 10.1186/s12941-022-00529-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of recently approved antibiotics against methicillin-resistant Staphylococcus aureus (MRSA) strains: A systematic review and meta-analysis

Abstract: Background Methicillin-resistant Staphylococcus aureus (MRSA) infections are considered an important public health problem, and treatment options are limited. Accordingly, in this meta-analysis, we analyzed published studies to survey in vitro activity of recently approved antibiotics against MRSA isolates. Methods We searched electronic databases; PubMed, Scopus, and Web of Science to identify relevant studies (until November 30, 2020) that have f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…The concentration of tedizolid that inhibited 90% of the present MRSA isolates (MIC 90 ) was 0.38 µg/mL, 2.6-fold lower than linezolid (MIC 90 , 1 µg/mL). Similarly, the findings of a recently published systematic review and meta-analysis demonstrated that the in vitro activity of tedizolid in 12,204 MRSA isolates was 0.25 and 0.50 µg/mL for MIC 50 and MIC 90, respectively [21]. A Korean multicenter study comparing the activities of tedizolid to those of linezolid for MRSA recovered from patients with SSTIs reported that the MIC 90 of tedizolid was 0.5 µg/mL, 4-fold lower than linezolid (MIC 90 , 2 µg/mL) [57].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The concentration of tedizolid that inhibited 90% of the present MRSA isolates (MIC 90 ) was 0.38 µg/mL, 2.6-fold lower than linezolid (MIC 90 , 1 µg/mL). Similarly, the findings of a recently published systematic review and meta-analysis demonstrated that the in vitro activity of tedizolid in 12,204 MRSA isolates was 0.25 and 0.50 µg/mL for MIC 50 and MIC 90, respectively [21]. A Korean multicenter study comparing the activities of tedizolid to those of linezolid for MRSA recovered from patients with SSTIs reported that the MIC 90 of tedizolid was 0.5 µg/mL, 4-fold lower than linezolid (MIC 90 , 2 µg/mL) [57].…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, a recent systematic review reported that the overall antibacterial activity of dalbavancin on 28,539 MRSA isolates was 0.060 and 0.120 µg/mL for MIC 50 and MIC 90 , respectively. Out of 11 studies, the pooled prevalence of dalbavancin susceptibility was 100% (95% CI: 100-100) [21]. It has been also shown that the dalbavancin MICs of VISA and heteroresistant VISA (hVISA) strains were 4-to 8-fold lower than vancomycin [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. aureus is a common cause of community and hospital-acquired infection ( 58 , 59 ). The WHO has regarded it as one of the primary clinical concerns, due to the global recognition of MRSA as a public health issue and the antibiotic resistance pattern of MRSA ( 60 ). The primary issue with MRSA is the incidence of multidrug resistance, which remains high ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…MRSA is the most studied bacteria in antibacterial assays employing NFs containing phytochemicals. Its widespread prevalence and ability to cause a range of infections, as well as its AMR to antibiotics, make MRSA a useful model organism for studying antibacterial agents and mechanisms of action [ 93 ].…”
Section: Nanofibersmentioning
confidence: 99%